Artificial neural network approach for modelling of mercury ions removal from water using functionalized CNTs with deep eutectic solvent - Fiyadh S.S.; Alomar M.K.; Jaafar W.Z.B.; Alsaadi M.A.; Fayaed S.S.; Koting S.B.; Lai S.H.; Chow M.F.; Ahmed A.N.; El-Shafie A. (MDPI AG, 2023)
adsorbent; carbon nanotube; deep eutectic solvent; mercury; politef; sodium hydroxide; solvent; unclassified drug; water; carbon nanotube; mercury; solvent; adsorption kinetics; Article; artificial neural network; contact time; correlation coefficient; diffusion; electricity; environmental parameters; Fourier transform infrared spectroscopy; inductively coupled plasma mass spectrometry; kinetics; mathematical phenomena; optical spectroscopy; oxidation; performance; pH; Raman spectrometry; zeta potential; adsorption; chemistry; procedures; water management; Adsorption; Mercury; Nanotubes, Carbon; Neural Networks, Computer; Solvents; Water Purification